The role of mesolimbic system and lateral habenular molecular targets (CB₁, GluA₁ and NK₁ receptors) in mitragyna speciosa korth (ketum) addiction in the mitragynine-sensitised swiss albino mice - Ismail, Nurul Iman Wan (2021)
There is a growing trend to use the leaves of Malaysian folklore medicinal plant Mitragyna speciosa Korth. (or ketum) for recreational high and as a self-medication alternative to traditional opiates, hence subjecting it to addictive liabilities. Mitragynine (ketum major alkaloid) is an atypical opioid agonist exhibiting complex psychostimulant and morphine-like analgesic effects, although the exact mechanisms remain unclear. In recent years, studies demonstrated a wide array of overlapping and integrated neuronal circuits in addiction, including the opioid-cannabinoid-glutamate AMPA-neurokinin-dopaminergic systems. This study aimed to demonstrate the involvement of the cannabinoid (CB1), glutamate (GluA1) and neurokinin (NK1) receptors in the hippocampus, ventral tegmental area (VTA) and lateral habenula (LHb) brain regions as the neurobiological bases of ketum abuse potential through its interaction with mitragynine. One hundred and twenty (n=120) male Swiss albino mice were subjected to 28-days (chronic) regimen with untreated and Tween-20 vehicle control, morphine sulphate, THC or mitragynine, either with/without coadministration with CB1, GluA1 or NK1 receptor antagonists (i.e. NIDA-41020, PhTx- 74 or RP-67580, respectively). The IntelliCage® system was used as the behavioural sensitisation setting to assess mice cognitive performances and addiction-like behaviours following chronic drug treatment. Findings revealed that chronic mitragynine exposure (incremental doses of 5 to 25 mg/kg) resulted in hyperlocomotion (p < 0.05), potentiated preference and persistence for natural reward (i.e. 10% sucrose) (p < 0.01), resistance to punishment (p < 0.05), and spatial learning memory deficit (p < 0.05), comparable to those observed in morphine- and THCsensitised mice (p > 0.05). The mitragynine-, morphine- and THC-induced spatial learning and memory impairments were attenuated by NIDA-41020 (p < 0.05), PhTx- 74 (p < 0.05) and RP-67580 (p < 0.05), suggesting the CB1, GluA1 and NK1 receptors putative role in the drugs’ mechanism of actions. The underlying adaptations in mice key brain mesolimbic areas, with regards to CB1, GluA1 and NK1 receptors, were investigated using immunohistochemistry, Western Blot and quantitative real-time PCR (qPCR) studies. Mitragynine-sensitised mice demonstrated enhanced CB1 receptor proteins and genes expression at hippocampus CA1 (p < 0.001) and VTA regions (p < 0.001). GluA1 receptor proteins and genes were also up-regulated at hippocampus CA1 regions (p < 0.001), whereas NK1 were up-regulated at the LHb (p < 0.05). These mitragynine-induced receptor up-regulations resembled those observed with chronic morphine (p > 0.05). Neuronal changes as seen in mitragynine- and morphine-sensitised mice appeared to be absent in drug paired with respective receptor antagonist groups, thus providing affirmative clues to the behavioural changes observed. Taken together, these findings demonstrate the seeming integrated role of brain CB1, GluA1 and NK1 receptors in mitragynine/ketum addictive liabilities, leading to behavioural and probable adaptive changes in the brain mesolimbic reward pathway. However, the extent and nature of these receptor interactions in ketum misuse remain unclear. The study findings lend the first correlative relationship that implicates drug molecular targets not previously known (i.e. cannabinoid-glutamate AMPA-neurokinin systems) in relation to chronic mitragynine misuse. This may also provide new insight to inform the phytomedicinal potentials that are linked to this plant.